A tumor-specific cleavable nanosystem of PEG-modified C60@Au hybrid aggregates for radio frequency-controlled release, hyperthermia, photodynamic therapy and X-ray imaging. (1st January 2016) - Shi, Jinjin; Chen, Zhaoyang; Wang, Lei; Wang, Binghua; Xu, Lihua; Hou, Lin; Zhang, Zhenzhong
Graphical abstract: Abstract: Taking advantages of fullerene (C60) and gold nanoparticles (AuNPs) for potentials in photodynamic therapy (PDT), drug delivery and radio frequency thermal therapy (RTT), a C60@Au hybrid nanocomposite was synthesized by chemical deposition of Au nanoparticles onto C60, and functionalized by PEG5000 via a pH cleavable hydrazone bond, making C60@Au-PEG keep the PEG on the surface of drug delivery system during circulation but dissociate PEG from the system after accumulation in tumor tissue, then doxorubicin (DOX) was loaded onto C60@Au-PEG with a very high drug loading efficiency. The release profiles of DOX from C60@Au-PEG/DOX showed strong dependences on radio frequency (RF). For the drug delivery, C60@Au-PEG/DOX afforded much higher antitumor efficacy owing to 8.6-fold higher DOX uptake of tumor than DOX. Besides, in this work, C60@Au-PEG/DOX not only served as a powerful RTT agent for RF-thermal ablation of tumor and a strong photosensitizer (PS) for PDT, but also as an X-ray contrast agent for tumor diagnosis. In the in vitro and in vivo studies, C60@Au-PEG/DOX showed excellent chemo-RF thermal-photodynamic therapeutic efficacy, RF-controlled drug releasing function, tumor targeting property, tumoral acid PEG dissociating character and X-ray imaging ability, demonstrating that there is a great potential of C60@Au-PEG/DOX for simultaneous diagnosis and therapy in cancer treatment. Statement of significance: A significant challenge in cancer therapy is to maximize the therapeutic efficacy and minimize the side effects. In the past decade, a lot of nanoparticles have been used as the carriers for efficient drug delivery. However, the design of drug delivery system (DDS) with stimuli-responsive controlled-release property, simultaneous diagnosis and therapy functions is still a challenge. Herein, we developed a new drug delivery system (C60@Au-PEG/DOX), and explored its applications in tumor therapy. The in vitro and in vivo results showed C60@Au-PEG/DOX could significantly improve the therapeutic efficacy and reduce the systemic toxicity through X-ray imaging guided locatable DOX release, photodynamic and photothermal therapies. These results are of interest as they demonstrate a multi-functional DDS for tumor theranostic applications.